‘It's All in the Context’: Indigenous Education for Pre-Service Teachers - Raegina Taylor (The Australian Journal of Indigenous Education, 2014)
This article describes how five pre-service teachers at similar stages of completion in their course at an Australian university responded to case studies on Indigenous education topics such as government policies, developing relationships, and teacher attitudes in the final assessment of a core unit of study. With the intent of encouraging student–teacher understandings to move beyond prior knowledge through dynamic scholarship, a case-study methodology was embedded across the pedagogical approach in an intensively taught Indigenous education core unit. The data consisted of an in-depth examination of five pre-service teachers’ assignments for levels of reflective language, and degree of orientation towards discourses in Indigenous education as associated with the assessment criteria. The findings support prior research in asserting core units in Indigenous education for pre-service teachers as paramount for developing teacher competencies, and argues careful consideration when deeming a graduate ready to teach according to the Australian Professional Standards for Teachers.